Every you, every me - Levithan, David; Farmer, Jonathan (New York : Alfred A. Knopf, 2011)
Evan is haunted by the loss of his best friend, but when mysterious photographs start appearing, he begins to fall apart as he starts to wonder if she has returned, seeking vengeance.
Keywords: Mental illness -- Fiction; Emotional problems -- Fiction; Interpersonal relations -- Fiction; Friendship -- Fiction; High schools -- Fiction; Schools -- Fiction